Fabrication of Platinum Functionalized Zinc Oxide Nanorods for High-Performance Acetylene Gas Sensor Integrated with Microheater - Kondalkar, Vijay V.; Thai Duy, Le; Seo, Hyungtak; Lee, Keekeun (2019 20th International Conference on Solid-State Sensors, Actuators and Microsystems and Eurosensors XXXIII, TRANSDUCERS 2019 and EUROSENSORS XXXIII, 2019)
The rapidly expanding infrastructure dictates the need for ubiquitous distributed low power, low-cost, high sensitivity gas sensor. In the past few decades, metal-oxide semiconductors have been investigated widely as gas sensing materials. However, their low sensitivity and high operating temperature (about 400-500 °C) have significant limitations. To resolve these problems, here, we report the Pt activated ZnO nanorods (NRs) as a highly sensitive material for MEMS compatible miniaturized acetylene gas sensor at low operating temperature. Further, before fabrication COMSOL simulation was performed to optimize the micro-heater design. The fabricated Pt functionalized ZnO NRs based sensor exhibits an ultrahigh response toward 1 ppm acetylene with faster response and recovery compared to state-of-the-art sensing characteristics.
Keywords: Gas sensing material; High operating temperature; High sensitivity gas sensor; Low operating temperature; Metal oxide semiconductor; Micro-heaters; Sensing characteristics; Zinc oxide nanorods; Acetylene sensor; Gas sensor; Micro-heater; Pt-decorated ZnO; Pt/ZnO